A Unique Solvent-Induced Structural Transformation of Two Acentric [Zn2（H2O）（Hdtim）2] Isomers - 党琴琴 冀芳 张献明 (Chinese journal of chemistry, 2012)
Solvent-induced structural transformation was observed in two layered supramolecular isomers of [Zn2（H2O）（Hdtim）2] （H3dtim--4,5-ditetrazoyl-imidazole）. Structural analyses revealed that the two isomers have the similar geometry of Zn, coordination mode of Hdtim2-, and topology. Their structural differences only arise from different arrangement of the layers which seemingly corresponds to cooperative clockwise and counter-clockwise 90° rotation of the adjacent layers. This is a quite unique solvent-dependent supramolecular isomerism in coordination polymers.